Psychogenic non epileptic events: The constant challenge of its diagnosis and treatment. - Quille Buendia, Adderly R (2020)
Psychogenic Non-Epileptic Events (PNEE) are paroxysmal episodes described as behavioral changes, sensory- sensitive disturbances, or motor manifestations that resemble epileptic seizures without showing underlying epileptiform activity, are not deliberately produced by the individual, and respond to multifactorial biopsychosocial mechanisms. Epidemiological information is limited due to the heterogeneous nature of the affected population, and to the limited accessibility to the video electroencephalogram (vEEG) necessary for its diagnosis. In such context, the convergence of two important elements is necessary: a detailed clinical history (clinical characteristics suggestive of PNEE, and identification of the associated factors), and the absence of electroencephalographic “ictal” changes in the vEEG. A psychological evaluation provides additional information, relevant for the diagnostic corroboration and management. The diagnosis must be made in a timely manner, to avoid complications in its evolution and treatment. A positive and encouraging attitude to the patient is vital when informing him/her of the diagnosis, as it also is the coordination between the treating neurologist and mental health professionals involved in the management and monitoring of the case. Cognitive behavioral psychotherapy, associated with psychopharmacotherapy -when needed-- constitute the most effective treatment approach for these patients. There are limited studies on the current epidemiological and clinical evolution of patients with PNEE in Latin America, and additional research regarding this problem is much needed, given its impact on the quality of life of the patients and on the cost of its management in the health care systems.